Bone Marrow Senescence and the Microenvironment of Hematological Malignancies - Charlotte Hellmich; Charlotte Hellmich; Jamie A. Moore; Kristian M. Bowles; Kristian M. Bowles; Stuart A. Rushworth (Frontiers in Oncology, 2020)
Senescence is the irreversible arrest of cell proliferation that has now been shown to play an important role in both health and disease. With increasing age senescent cells accumulate throughout the body, including the bone marrow and this has been associated with a number of age-related pathologies including malignancies. It has been shown that the senescence associated secretory phenotype (SASP) creates a pro-tumoural environment that supports proliferation and survival of malignant cells. Understanding the role of senescent cells in tumor development better may help us to identify new treatment targets to impair tumor survival and reduce treatment resistance. In this review, we will specifically discuss the role of senescence in the aging bone marrow (BM) microenvironment. Many BM disorders are age-related diseases and highly dependent on the BM microenvironment. Despite advances in drug development the prognosis particularly for older patients remains poor and new treatment approaches are needed to improve outcomes for patients. In this review, we will focus on the relationship of senescence and hematological malignancies, how senescence promotes cancer development and how malignant cells induce senescence.